KONSEP ILMU DALAM PERSPEKTIF PEMIKIR PENDIDIKAN ISLAM - Dedik Dedik (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2021)
Islamic education creatively cultivates human instruments as a means of attaining knowledge from the most elementary instruments, namely the five senses, mind and heart to make students believe in Allah and carry out their duties as servants of Allah and khalifatullah who prosper the earth and become a blessing for nature.